1988
DOI: 10.1111/j.1444-0938.1988.tb03850.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pupil size on kinetic visual field measurements

Abstract: We determined visual field size as a function of pupil size by repeated measurements of Goldmann fields with an I2 target in the same subjects using contact lenses with different sized artificial pupils. Increasing pupil size from 3 to 6.8 mm increases visual field size from 2.79 to 3.34 steradians, an average increase of 19.7 per cent; a control experiment suggested that the major part of this effect can be explained by reduction of retinal illuminance produced by the variation in pupil size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…I have tried to reconcile the optical predictions in this paper with empirical perimetry findings by other researchers. [3][4][5][6][7][8] Previous researchers have found that semi-opaque periphery contact lenses do not affect field measurements obtained with clinically Contact lens field restriction Carkeet used static perimeters, 6-8 but the optical theory in this paper suggests that such lenses cause the largest retinal illuminance drop for field regions wider than those measured by clinical perimeters. Therefore, future empirical studies of such lenses could involve field regions wider than 60 to 75 degrees.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…I have tried to reconcile the optical predictions in this paper with empirical perimetry findings by other researchers. [3][4][5][6][7][8] Previous researchers have found that semi-opaque periphery contact lenses do not affect field measurements obtained with clinically Contact lens field restriction Carkeet used static perimeters, 6-8 but the optical theory in this paper suggests that such lenses cause the largest retinal illuminance drop for field regions wider than those measured by clinical perimeters. Therefore, future empirical studies of such lenses could involve field regions wider than 60 to 75 degrees.…”
Section: Discussionmentioning
confidence: 76%
“…3 By using kinetic perimetry, it has been shown that such lenses can constrict visual fields 3 but previous literature contains almost no discussion of the optical theory behind the visual field restriction by such lenses. Some authors have measured kinetic visual field restriction with cosmetic contact lenses that have semi-opaque peripheries (that is, a matrix of opaque dots which alter iris colour appearance) 4,5 although two studies have reported that such lenses do not significantly affect static visual fields.…”
mentioning
confidence: 99%
“…Figure 5 then suggests that under these conditions the field boundary should lie at field angles of about 60°, which is compatible with the trend of the observed loss in sensitivity at field angles beyond 30° (Figure 7). For comparison, Gabriel et al, 30 using kinetic perimetry and a 31.8 cd m À2 Goldmann I-0.11°stimulus, found that the area of the visual field was limited to about 2.8 steradians in subjects wearing contact lenses with a 3 mm clear aperture, corresponding to a field radius of about 54°.…”
Section: Discussionmentioning
confidence: 99%
“…It has since been suggested that it might be useful for presbyopic patients who have already been implanted with multifocal IOLs but who find that their vision is poor. Since the pinhole is very close to the natural pupil, it has negligible effect upon the extent of the visual field although sensitivity is, of course, lost because of the reduced retinal illuminance …”
Section: Surgical Pinhole Variants: Corneal Inlays and Iolsmentioning
confidence: 99%